2000
DOI: 10.1108/02621710010308135
|View full text |Cite
|
Sign up to set email alerts
|

Business ethics and social responsibility in transition economies

Abstract: The newly developed market‐oriented system in Hungary requires new values, different abilities, and more sensitivity to a wide variety of issues on the part of corporate leadership. The nature of these values and abilities will more than likely vary depending on the industry. The purpose of this study was to examine the view of business ethics and social responsibility among Hungarian managers in both the business and non‐business sectors. The results indicate differences between the examined groups and divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 20 publications
2
30
0
3
Order By: Relevance
“…Thirteen behaviours were identified from the comments and represented in 4 clusters of social responsibility behaviours, as shown in Table 4. The findings of the current interviews indicated some overlap with those of Fülöp et al (2000).…”
Section: Socially Responsible Practicesmentioning
confidence: 88%
See 1 more Smart Citation
“…Thirteen behaviours were identified from the comments and represented in 4 clusters of social responsibility behaviours, as shown in Table 4. The findings of the current interviews indicated some overlap with those of Fülöp et al (2000).…”
Section: Socially Responsible Practicesmentioning
confidence: 88%
“…We follow Fülöp et al (2000)'s definition of social responsibility as "the positive activities a company undertakes in the society in which it operates" including responsibility towards customers, employees and the public. When the concept was first developed more than twenty years ago, organisations found it difficult to operationalise it in their business practices, as it required sacrifices to be made on the financial level.…”
Section: Ethical and Socially Responsible Practices In Smesmentioning
confidence: 99%
“…The management literature generally is increasingly highlighting the importance of ethical management behaviours and the researcher made reference to this literature when defining this competency domain (e.g., Fülöp et al, 2000;Hornsby et al, 1994). Specifically, the definition of ethical business behaviour proposed by Lewis (1985) was used to define ethical practices as behaviours that indicate the use of "rules, standards, codes, or principles which provide guidelines for morally right behaviour and truthfulness in specific situations" (p. 381).…”
Section: Resultsmentioning
confidence: 99%
“…However, recently, organisations' leaders have started to acknowledge the importance of being socially responsible in business affairs. For example, Fülöp et al (2000) found that there is a growing commitment to social responsibility among smaller firms, which is comparable to that of larger firms. Specifically, they found that small firms have demonstrated willingness to make arrangements to meet the requirements of social responsibility especially to their customers, their employees, and the public.…”
Section: Ethical and Socially Responsible Practices In Smesmentioning
confidence: 99%
See 1 more Smart Citation